Representaciones sociales de los estudiantes universitarios en Gestión Cultural sobre los avances de la disciplina en el sureste de México - Frías López, Aurora Kristell (Periférica Internacional. Revista para el análisis de la cultura y el territorio, 2020)
La profesionalización de la Gestión Cultural en México ha avanzado en las últimas dos décadas y se ha logrado debido al interés de las instituciones universitarias tanto públicas como privadas. En el sureste de México, la universidad pública de Tabasco fue una de las pioneras en el país en la oferta de la licenciatura en Desarrollo Cultural en el 2007, la cual se reestructuró en 2017 con el nombre de Gestión y Promoción de la Cultura. De ahí se deriva este estudio el cual tiene como actores sociales a los estudiantes que conforman las primeras generaciones de esta nueva oferta universitaria en modalidad presencial escolarizada. En este artículo se identifi can las representaciones sociales de los estudiantes respecto a su disciplina, las cuales tienen como núcleo central, la preocupación por el distanciamiento de la sociedad con la cultura, lo cual, dicen, repercutirá en su inserción al campo laboral. Palabras clave: gestión cultural, universidad pública, estudiantes, representaciones sociales. Social representations of university students in Cultural Management on the advances of the discipline in the southeast of Mexico Abstract: This research aims to identify the social representations of students in Management and Promotion of Culture at a public university in Tabasco at southeastern Mexico. It was analyzed using the theory of social representations. The methodology used was quantitative using the survey as the data collection technique. Regarding the social actors under study, we worked with the fi nite population, through the non-probabilistic technique. The social representations of the students of the fi rst generations of said degree have as a central nucleus, the concern for the current distancing of society with culture, so they consider that their professional duty is to create a link through projects of Intervention projects that manage to change these perceptions of the people of their entity, which is a challenge they acquire as students of cultural management, and very soon as graduates. The limitations of the research are derived in terms of the number of population with which it was worked, which was the one belonging to a public university, remaining outside those dependent on government institutions that are focused on artistic creation. The lines through which this research work can be extended is the follow-up of the fi rst generations of graduates and their insertion into the labor field. Keywords: cultural Management, public university, students, Social representations. Artículo recibido: 25/09/2020 / Artículo aceptado: 28/09/2020.